Effect of Treadmill Exercise Using 80% Intensity of Six Minute Walk Test on Walking Distance and Quality of Life in Moderate Stage Chronic Obstructive Pulmonary Disease Patients - Arisanti, Farida; Vitriana, Vitriana; Santoso, Prayudi (Majalah Kedokteran Bandung, 2016)
Skeletal muscle dysfunction poses as one of the systemic manifestation of chronic obstructive pulmonary disease (COPD) in the impact of inactivity and deconditioning from early fatigue to the end of declining quality of life (QoL). Giving pulmonary rehabilitation program of treadmill exercise will overcome the problem, but standard method for moderate stage of COPD is not yet available. This study aimed to evaluate the effect of treadmill exercise using 80% intensity of six minute walk test on walking distance and QoL in moderate stage COPD in order to overcome muscle dysfunction. Samples were taken from Physical Medicine and Rehabilitation and Respirology subdivision of Internal Medicine outpatient clinic of Dr. Hasan Sadikin General Hospital Bandung, from March 2012–April 2013. Data analysis was tested using t-test for comparison of two independent mean data. Otherwise, non parametric test of Mann Whitney and Wilcoxon Match Pair test. Thirty three subjects of moderate stage COPD were divided into 2 groups (intervention and control). Intervention group received treadmill exercise with 80% intensity from preliminary 6MWT for 30–60 minutes/session, 3 session/week for 6 weeks. Significant increase on walking distance was found in intervention group (70.66 m) compared to control group (7.43 m) after 6 weeks (p≤0.05). QoL using St. George Respiratory Questionnaire (SGRQ) showed significant decrease in intervention group for all components in the end of 6 weeks (total p=0.0038, symptoms p=0.0162, activities p=0.0043 and impact p=0.0057, p≤0.05). Eighty percent intensity of 6MWT in treadmill exercise for 6 weeks was well tolerated and could overcome skeletal muscle dysfunction in moderate stage COPD. It also revealed higher values in aerobic capacity and QoL compared to previous studies. In conclusion, treadmill exercise using 80% intensity of 6MWT provides further walking distance and higher QoL compared to control  in moderate stage COPD. [MKB. 2016;48(2):105–11]Key words: Moderate stage COPD, quality of life, treadmill exercise, 6MWDPengaruh Latihan Erobik Menggunakan Treadmill dengan Intensitas 80% Uji Jalan 6 Menit terhadap Jarak Tempuh dan Kualitas Hidup Pasien PPOK Derajat SedangDisfungsi otot rangka merupakan salah satu manifestasi sistemik penyakit paru obstruktif kronik (PPOK), menyebabkan penderita mengalami inaktivitas dan dekondisi akibat kelelahan dini sehingga menurunkan kualitas hidupnya. Latihan erobik menggunakan treadmill merupakan modalitas dalam rehabilitasi PPOK untuk mengatasinya, namun hingga saat ini belum ada metode baku pada PPOK derajat sedang. Penelitian ini bertujuan menilai pengaruh latihan erobik menggunakan treadmill dengan intensitas 80% uji jalan 6 menit terhadap jarak tempuh dan kualitas hidup pada pasien PPOK derajat sedang. Penelitian ini dilakukan di Departemen Ilmu Kedokteran Fisik dan Rehabilitasi Fakultas Kedokteran Universitas Padjadjaran/Rumah Sakit Dr. Hasan Sadikin Bandung periode Maret 2012–April 2013. Naracoba berjumlah 33 orang, dibagi menjadi kelompok kontrol dan perlakuan. Latihan dilakukan dengan intensitas 80% kecepatan uji jalan 6 menit, 30–60 menit/sesi, 3x/minggu selama 6 minggu. Terjadi peningkatan bermakna jarak tempuh (p≤0,05) dan penurunan nilai St. George Respiratory Questionnaire (SGRQ) di seluruh komponennya (total, dampak, gejala dan aktivitas, p≤0,05) kelompok perlakuan dibanding dengan kontrol setelah 6 minggu latihan. Latihan erobik menggunakan treadmill dengan intensitas 80% kecepatan uji jalan 6 menit selama 6 minggu ditoleransi dengan baik dan dapat memperbaiki disfungsi otot rangka pada pasien PPOK derajat sedang. Simpulan, latihan erobik menggunakan treadmill dengan intensitas 80% dari uji jalan 6 menit memberikan peningkatan jarak tempuh dan kualitas hidup dibanding dengan kontrol pada PPOK derajat sedang. [MKB. 2016;48(2):105–11]Kata kunci: Jarak tempuh uji jalan 6 menit, kualitas hidup, latihan treadmill, PPOK derajat sedang